Baseline Susceptibility and Cross-Resistance of HearNPV in Helicoverpa armigera (Lepidoptera: Noctuidae) in Brazil - Dionei Schmidt Muraro; Thaini M. Gonçalves; Douglas Amado; Marcelo F. Lima; Holly J. R. Popham; Paula G. Marçon; Celso Omoto (Insects, 2022)
The marked adoption of bioinsecticides in Brazilian agriculture in recent years is, at least partially, explained by the increasingly higher levels of insect pest resistance to synthetic insecticides. In particular, several baculovirus-based products have been registered in the last 5 years, including Helicoverpa armigera nucleopolyhedrovirus (HearNPV: Baculoviridae: Alphabaculovirus (Armigen®)). Understanding the susceptibility of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) to HearNPV is an important step toward development of robust Integrated Pest Management (IPM) and Insect Resistance Management programs (IRM) aimed at managing this serious insect pest. In this study, droplet feeding bioassays were used to characterize the baseline susceptibility to HearNPV (Armigen®) in H. armigera populations collected from major soybean and cotton-growing regions in Brazil. We defined and validated a diagnostic concentration for susceptibility monitoring of H. armigera populations to HearNPV. Additionally, cross-resistance between HearNPV and the insecticides flubendiamide and indoxacarb was evaluated by testing HearNPV in a susceptible strain and in resistant strains of H. armigera to these insecticides. A low interpopulation variation of H. armigera to HearNPV was detected. The LC50 values ranged from 1.5 × 105 to 1.1 × 106 occlusion bodies (OBs) per mL (7.3-fold variation). The mortality rate at the identified diagnostic concentration of 6.3 × 108 OBs/mL, based on the calculated LC99, ranged from 98.6 to 100% in populations of H. armigera collected from 2018 to 2020. No cross-resistance was detected between HearNPV and flubendiamide or indoxacarb. These results suggest that HearNPV (Armigen®) can be an effective tool in IPM and IRM programs to control H. armigera in Brazil.